The Salving of the "Fusi Yama": A Post-War Story of the Sea - Westerman, Percy F. (Percy Francis), 1876-1959; Hodgson, E. S. (Edward Smith), 1866-1937 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Salving of the 'Fusi Yama': A Post-War Story of the Sea" by Percy F. Westerman is a novel written in the early 20th century. The book follows the adventures of ex-officers who embark on a treasure-hunting expedition after World War I, focusing on the main characters Jack Villiers and Bobby Beverley as they navigate post-war uncertainties and seek thrilling new opportunities. The narrative showcases their aspirations and the challenges they face as they venture into a world filled with danger and intrigue. The opening of the story introduces us to Jack Villiers and Bobby Beverley, both recently demobilized from the Royal Navy and struggling to find their footing in civilian life. They express their reluctance to settle into ordinary jobs, yearning for action and adventure. Their discussions are interrupted by a peculiar advertisement seeking ex-service members for a potentially exciting venture, sparking their interest. As they navigate the aftermath of the war, they encounter Sir Hugh Harborough, who lays the foundation for a treasure-hunting mission centered on the sunken ship "Fusi Yama," said to be carrying a fortune in gold. The beginning sets a vibrant tone of camaraderie and the pursuit of adventure, hinting at the thrilling escapades that lie ahead. (This is an automatically generated summary.)
Release date is 2016-06-15
Produced by R.G.P.M. van Giesen. Thank you, Iain Somerville!
Keywords: Sea stories; Treasure troves -- Juvenile fiction; Warships -- Salvaging -- Juvenile fiction